Entropy of coupled Klein-Gorden Field in FLRW space - Dhungel, Prem Raj; Sharma, Sanat Kumar; Khanal, Uday Raj (Scientific World, 2023)
The coupled Klein-Gordan (KG) field in FLRW space-time has been further studied to explore its effect on entropy. The modifications in pressure and density and hence entropy due to coupling have been calculated. There is an indication seen that the introduction of the coupling contributes to the generation of entropy in the KG field which may probably explain the large entropy of the universe.